2019
DOI: 10.1039/c8ta11375k
|View full text |Cite
|
Sign up to set email alerts
|

The combination of intercalation and conversion reactions to improve the volumetric capacity of the cathode in Li–S batteries

Abstract: Hollow VO2@S microspheres were designed as cathode materials with high volumetric capacity by combining the intercalation and conversion mechanisms together.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…of V=S, V—S bonds, [ 36 ] respectively. Above all, both the V2p and S2p patterns indicate that the formation of chemical bonds between VO 2 (M) and S 8 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…of V=S, V—S bonds, [ 36 ] respectively. Above all, both the V2p and S2p patterns indicate that the formation of chemical bonds between VO 2 (M) and S 8 .…”
Section: Resultsmentioning
confidence: 99%
“…[ 42 ] Also, the oxidation peaks (iii and iv) at roughly 2.36 and 2.41 V are attributed to the converse conversion reactions of the final discharge products (lithium sulfides) to soluble polysulfides and further to the original active sulfur, respectively. [ 29,36 ] Interestingly, Li‐VO 2 (M)@CFs/S cathode with a slight shift to higher potential during the discharge process compared to the VO 2 (M)@CFs/S cathode shows its faster redox reactions. The much sharper peak ii of Li‐VO 2 (M)@CFs/S cathode suggests the enhanced conversion from LiPSs to insoluble Li 2 S, anticipating that the structure will upgrade the electrochemical performance of Li‐S batteries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Xu et al have demonstrated O vacancies on ultrathin niobic acid could hinder the LiPSs redox conversion kinetics. [74] In the study, the decreased performance of LiÀ S batteries was mainly due to the decreased electrical conductivity and the weakened adsorption of LiPSs by the high O vacancy concentration.…”
Section: Sulfur Cathodementioning
confidence: 91%
“…Besides the metal oxides mentioned above, many other metal oxides such as SiO 2 , [101] Co 3 O 4 , [102] MgO, [103] Fe 2 O 3 , [104] Al 2 O 3 , [103a,105] V 2 O 5 , [106] Ta 2 O 5−x , [107] V 2 O 3 , [108] VO 2 , [109] ZnO, [110] WO 3 , [111] CaO, [103a] MoO 2 , [112] MoO 3 , [113] La 2 O 3 , [103a] SnO 2 , [114] Nb 2 O 5 , [115] ZnCo 2 O 4 , [116] NiFe 2 O 4 , [117] Nb 18 W 16 O 93 , [118] La 0.8 Sr 0.2 MnO 3 , [119] perovskite Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3−δ , [120] and Figure 13. a) Schematic of synthetic process for TiO@C-HS/S spheres.…”
Section: The S Tmentioning
confidence: 99%